Controlling Self‐Assembly in Gyroid Terpolymer Films By Solvent Vapor Annealing. Issue 46 (5th September 2018) - Dolan, James A.; Korzeb, Karolina; Dehmel, Raphael; Gödel, Karl C.; Stefik, Morgan; Wiesner, Ulrich; Wilkinson, Timothy D.; Baumberg, Jeremy J.; Wilts, Bodo D.; Steiner, Ullrich; Gunkel, Ilja
Abstract: The efficacy with which solvent vapor annealing (SVA) can control block copolymer self‐assembly has so far been demonstrated primarily for the simplest class of copolymer, the linear diblock copolymer. Adding a third distinct block—thereby creating a triblock terpolymer—not only provides convenient access to complex continuous network morphologies, particularly the gyroid phases, but also opens up a route toward the fabrication of novel nanoscale devices such as optical metamaterials. Such applications, however, require the generation of well‐ordered 3D continuous networks, which in turn requires a detailed understanding of the SVA process in terpolymer network morphologies. Here, in situ grazing‐incidence small‐angle X‐ray scattering (GISAXS) is employed to study the self‐assembly of a gyroid‐forming triblock terpolymer during SVA, revealing the effects of several key SVA parameters on the morphology, lateral order, and, in particular, its preservation in the dried film. The robustness of the terpolymer gyroid morphology is a key requirement for successful SVA, allowing the exploration of annealing parameters which may enable the generation of films with long‐range order, e.g., for optical metamaterial applications. Abstract : Triblock terpolymers can self‐assemble into various 3D network structures, such as the gyroid . Controlled annealing of gyroid terpolymer films, limiting defect formation, is essential for several applications. This article uncovers a route toward long‐range order in gyroid films through in situ grazing‐incidence small‐angle X‐ray scattering (GISAXS) during solvent vapor annealing.